2013
DOI: 10.1094/phyto-11-12-0309-r
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Peroxide Accumulation and Transcriptional Changes in Grapevines Recovered from Flavescence Dorée Disease

Abstract: Flavescence dorée (FD) is considered one of the most severe phytoplasma diseases affecting grapevine. The spontaneous, complete, and stable remission of the symptoms of FD (recovery) is a phenomenon that may occur in infected grapevines. The molecular bases of this phenomenon are still unclear, although some works suggest that recovery could be linked to the accumulation of hydrogen peroxide (H2O2). Several genes coding for enzymes involved in H2O2 metabolism, in the ascorbate-glutathione cycle, defense respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 45 publications
8
46
0
Order By: Relevance
“…Overall, there was no clear correlation between the location of plants that recovered and those showing symptoms in the previous year, suggesting that plant recovery was not significantly influenced by nearby infections. Indeed, plant recovery is driven by a defense mechanism of the infected plant itself (Musetti et al, 2007; Gambino et al, 2013; Santi et al, 2013) that has no relations with the sanitary status of neighboring plants. Tracking recovered plants against newly infected plants in the following years, demonstrated that recovered plants did not reinfect over the time scale analyzed here.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, there was no clear correlation between the location of plants that recovered and those showing symptoms in the previous year, suggesting that plant recovery was not significantly influenced by nearby infections. Indeed, plant recovery is driven by a defense mechanism of the infected plant itself (Musetti et al, 2007; Gambino et al, 2013; Santi et al, 2013) that has no relations with the sanitary status of neighboring plants. Tracking recovered plants against newly infected plants in the following years, demonstrated that recovered plants did not reinfect over the time scale analyzed here.…”
Section: Resultsmentioning
confidence: 99%
“…Infected grapevines usually show symptoms the year after infection but longer incubation periods are possible depending on plant response to the pathogen and environmental factors (Caudwell et al, 1987). Grapevines can recover from FD disease at a rate that depends on the grapevine cultivar (Bellomo et al, 2007; Morone et al, 2007; Belli et al, 2010), but the underlying physiological and molecular mechanisms are not yet fully understood (Caudwell and Larrue, 1986; Musetti et al, 2007; Margaria and Palmano, 2011; Gambino et al, 2013; Vitali et al, 2013). In our earlier studies, we found that S. titanus could not acquire FD from asymptomatic and recovered vines (Galetto et al, 2014), and that vector acquisition efficiency was low when feeding on plants with low phytoplasma load (Bressan et al, 2005b; Galetto et al, 2016); in those experiments, it was found that recovered plants were symptomless and returned negative PCR test against FD phytoplasma (Galetto et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the hormone jasmonic acid (JA) is known to be involved in regulating plant response to stress; down‐regulation of genes involved in its biosynthesis was observed in FDp‐infected grapevine leaves (Gambino et al . ). Interestingly, JA level was significantly reduced by flavonoid accumulation in Arabidopsis (Pourcel et al .…”
Section: Discussionmentioning
confidence: 97%
“…The T 0 and T 1 transgenic plants harboring the full length cDNA of OsRGLP1 were similar to the wild-type plants in morphology; however unlike control, the six months old transgenic plants showed hypersensitive response-like necrotic lesions on older leaves when kept at day/night temperatures of 30/24 C and under direct sunlight in the absence of a challenge with any microbe. As GLPs are connected with OXO and/or superoxide dismutase activities resulting in production of H 2 O 2 (Gambino et al 2013), it was speculated that the product of OsRGLP1 may possess either one or both activities and generate H 2 O 2 resulting in hypersensitive reaction (HR)-like lesions under a high temperature and sunlight. When leaf disks from the transgenic and control plants were subjected to DAB staining, the transgenic leaf disks exhibited a higher content of H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%